2017
DOI: 10.26791/sarkiat.342143
|View full text |Cite
|
Sign up to set email alerts
|

Okul Öncesi̇ Değerler Eği̇ti̇mi̇nde Kullanilan Yöntem Ve Tekni̇kler (Ni̇tel Bi̇r Araştirma)

Abstract: Okul öncesinde değerler bazı yöntem ve tekniklerle öğretilebilir mi? Okul öncesinde değerler eğitimi için hangi yöntem ve teknikler kullanılmalıdır? Okul öncesi değerler eğitiminde kullanılan yöntem ve teknikler nelerdir? Soruları etrafında bu araştırma odaklanmaktadır. Araştırma nitel olarak tasarlanmıştır. Bu araştırmanın deseni olgubilim (fenomenoloji)'dir. Bu araştırmada amaçlı örnekleme tekniği kullanılmıştır. Evren açısında Mardin il merkezi ve örneklem için de okul öncesi öğretmenleri tercih edilmiştir.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
0
2
0
2
Order By: Relevance
“…There is a lack of literature examining the development of values specifically through sports such as gymnastics. However, existing studies on values in education highlight concepts such as respect, responsibility, love, tolerance, and cooperation as essential for children's development (Akto & Akto, 2017;Arıcı & Bartan, 2019;Ogelman & Sarıkaya, 2015;Yıldız, Elibol & Ada, 2021). These concepts align with the scale and subdimensions used in our study.…”
Section: Discussionsupporting
confidence: 63%
“…There is a lack of literature examining the development of values specifically through sports such as gymnastics. However, existing studies on values in education highlight concepts such as respect, responsibility, love, tolerance, and cooperation as essential for children's development (Akto & Akto, 2017;Arıcı & Bartan, 2019;Ogelman & Sarıkaya, 2015;Yıldız, Elibol & Ada, 2021). These concepts align with the scale and subdimensions used in our study.…”
Section: Discussionsupporting
confidence: 63%
“…Thompson (2011) found that teachers mostly preferred storytelling and role model techniques in values education. Akto and Akto (2017) determined that pre-school teachers use methods and techniques such as educational games, reading books, question-answer, drama and discussion in values education. The methods and techniques that can be employed in values education may vary according to teachers' practices.…”
Section: Discussionmentioning
confidence: 99%
“…Etkin bir öğretim için öğretmenin uygulayacağı çok sayıda yöntem ve teknik mevcuttur. Yöntem ve teknik seçiminde programın niteliği, öğrenci grubunun tutumları, öğretmen ve öğrencilerin kişilikleri, sınıf atmosferi ve çevresel faktörler etkili olmaktadır (Akto ve Akto, 2017). Her bir yöntemin geliştirilme kaygısı farklı olduğundan, bir konuda etkili öğrenme için yöntemlerden bir tanesi faydalı olurken, bir diğerinin herhangi bir etkisi olmayabilir.…”
Section: Adı Uygulama şEkli Faydalarıunclassified